Exonization of a deep intronic long interspersed nuclear element in Becker muscular dystrophy - Xie, Zhiying; Liu, Chang; Lu, Yanyu; Sun, Chengyue; Liu, Yilin; Yu, Meng; Shu, Junlong; Meng, Lingchao; Deng, Jianwen; Zhang, Wei; Wang, Zhaoxia; Lv, He; et al. (Frontiers in Genetics, 2022)
The precise identification of pathogenic DMD variants is sometimes rather difficult, mainly due to complex structural variants (SVs) and deep intronic splice-altering variants. We performed genomic long-read whole DMD gene sequencing in a boy with asymptomatic hyper-creatine kinase-emia who remained genetically undiagnosed after standard genetic testing, dystrophin protein and DMD mRNA studies, and genomic short-read whole DMD gene sequencing. We successfully identified a novel pathogenic SV in DMD intron 1 via long-read sequencing. The deep intronic SV consists of a long interspersed nuclear element-1 (LINE-1) insertion/non-tandem duplication rearrangement causing partial exonization of the LINE-1, establishing a genetic diagnosis of Becker muscular dystrophy. Our study expands the genetic spectrum of dystrophinopathies and highlights the significant role of disease-causing LINE-1s insertions in monogenic diseases.